You should have put a picture of the question so ppl could see what your talkin bout
It would equal 93.2057mph
Answer:
<u>Q/ Draw a line ; Ans; </u>
![\frac{9}{5} —>1 \frac{4}{5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B9%7D%7B5%7D%20%20%E2%80%94%3E1%20%5Cfrac%7B4%7D%7B5%7D%20%20)
*explain ; We put the 5 in the denominator and 5 multiply 1 + 4 so equal 9 so the choice 9/5 .
Ans; 7/3—> 2 1/3
*explain ; We put the 3 in the denominator and 3 multiply 2 + 1 so equal 7 so the choice 7/3 .
Ans; 12/10 —> 1 1/5
*explain; simple (12 and 10) ÷ 2 so equal 6/5
We put the 5 in the denominator and 5 multiply 1 + 1 so equal 6 so the choice 6/5 =12/10 .
![\frac{12 \div 2}{10 \div 2} = \frac{6}{5} = 1 \frac{1}{5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B12%20%5Cdiv%202%7D%7B10%20%5Cdiv%202%7D%20%20%3D%20%20%5Cfrac%7B6%7D%7B5%7D%20%20%3D%201%20%5Cfrac%7B1%7D%7B5%7D%20)
<u>Q/ Compare the fractions;Ans;</u>
![\frac{2}{3} < \frac{14}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3%7D%20%20%3C%20%20%5Cfrac%7B14%7D%7B6%7D%20%20)
* explain; 2/3 = 0.66 and 14/6=2.33 so 2.33 greater from 0.66 so 14/6 greater from 2/3 .
![\frac{3}{8} < \frac{8}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B8%7D%20%20%3C%20%20%5Cfrac%7B8%7D%7B3%7D%20)
* explain; 3/8 = 0.375 and 8/3=2.666 so 2.666 greater from 0.375 so 8/3 greater from 3/8 .
![2 \frac{1}{6} > \frac{5}{9}](https://tex.z-dn.net/?f=2%20%20%5Cfrac%7B1%7D%7B6%7D%20%20%3E%20%20%5Cfrac%7B5%7D%7B9%7D%20)
* explain; 2 1/6 —> We put the 6 in the denominator and 6 multiply 2 + 1 so equal 13 so equal 13/6
13/6 = 2.16 and 5/9=0.55 so 2.16 greater from 0.55 so 13/6 = 2 1/6 greater from 5/9 .
<u>Q/Add; Ans;</u>
![\frac{7}{8} + \frac{5}{8} = \frac{7 + 5}{8} = \frac{12}{8} = \frac{3}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B7%7D%7B8%7D%20%20%2B%20%20%5Cfrac%7B5%7D%7B8%7D%20%20%3D%20%20%5Cfrac%7B7%20%2B%205%7D%7B8%7D%20%20%3D%20%20%5Cfrac%7B12%7D%7B8%7D%20%20%3D%20%20%5Cfrac%7B3%7D%7B2%7D%20%3C%2Fp%3E%3Cp%3E)
![\frac{1}{9} + \frac{2}{3} \\ \\ \frac{1}{9} + \frac{6}{9} = \frac{ 1+6 }{9} = \frac{7}{9}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B9%7D%20%20%2B%20%20%5Cfrac%7B2%7D%7B3%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B1%7D%7B9%7D%20%20%2B%20%20%5Cfrac%7B6%7D%7B9%7D%20%20%3D%20%20%5Cfrac%7B%201%2B6%20%7D%7B9%7D%20%20%3D%20%20%5Cfrac%7B7%7D%7B9%7D%20)
<u>Q/Subtract; Ans;</u>
![\frac{6}{7} - \frac{4}{7} = \frac{6 - 4}{7} = \frac{2}{7}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7B7%7D%20%20-%20%20%5Cfrac%7B4%7D%7B7%7D%20%20%3D%20%20%5Cfrac%7B6%20-%204%7D%7B7%7D%20%20%3D%20%20%5Cfrac%7B2%7D%7B7%7D%20)
![\frac{7}{3} - \frac{2}{9} \\ \\ \frac{21}{9} - \frac{2}{9} = \frac{21 - 2}{9} = \frac{19}{9}](https://tex.z-dn.net/?f=%20%5Cfrac%7B7%7D%7B3%7D%20%20-%20%20%5Cfrac%7B2%7D%7B9%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B21%7D%7B9%7D%20%20-%20%20%5Cfrac%7B2%7D%7B9%7D%20%20%3D%20%20%5Cfrac%7B21%20-%202%7D%7B9%7D%20%20%3D%20%20%5Cfrac%7B19%7D%7B9%7D%20)
<u>Q/ Multiply;Ans;</u>
![\frac{1}{5} \times \frac{1}{2} = \frac{1}{10}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B5%7D%20%20%5Ctimes%20%20%5Cfrac%7B1%7D%7B2%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B10%7D%20)
![\frac{2}{3} \times \frac{3}{8} = \frac{6}{24} = \frac{1}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3%7D%20%20%5Ctimes%20%20%5Cfrac%7B3%7D%7B8%7D%20%20%3D%20%20%5Cfrac%7B6%7D%7B24%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B4%7D%20)
<u>Q/Divide;Ans;</u>
![\frac{3}{4} \div \frac{2}{5} \\ \\ \frac{3}{4} \times \frac{5}{2} = \frac{15}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20%20%5Cdiv%20%20%5Cfrac%7B2%7D%7B5%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B3%7D%7B4%7D%20%20%5Ctimes%20%20%5Cfrac%7B5%7D%7B2%7D%20%20%3D%20%20%5Cfrac%7B15%7D%7B8%7D%20)
![\frac{8}{9} \div \frac{1}{3} \\ \\ \frac{8}{9} \times \frac{3}{1} = \frac{24}{9} = \frac{8}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B8%7D%7B9%7D%20%20%5Cdiv%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B8%7D%7B9%7D%20%20%5Ctimes%20%20%5Cfrac%7B3%7D%7B1%7D%20%3D%20%20%20%5Cfrac%7B24%7D%7B9%7D%20%20%3D%20%20%5Cfrac%7B8%7D%7B3%7D%20)
I hope I helped you^_^
Answer:
Step-by-step explanation:
Answer:
(f + g)(x) = x^2 + 3x - 6
Step-by-step explanation:
Given f(x) = x^2 + x − 2 and g(x) = 2x − 4
Plug in:
(f + g)(x) = x^2 + x − 2 + 2x − 4
(f + g)(x) = x^2 + 3x - 6